Global journalism practice and new media performance / [edited by] Yusuf Kalyango, Jr., Ohio University, USA ; David H. Mould, Ohio University, USA. - Kalyango, Yusuf; Mould, David H. (David Harley), 1949- (Palgrave Macmillan, 2014)
There is a growing need to understand how journalism continues to be practiced around the world from those who practice and teach the craft. Global Journalism Practice and New Media Performance provides an overview of new and traditional media in their political, economic and cultural contexts while exploring the role of journalism practice and media education. The authors examine media systems in 16 countries: Armenia, China, Colombia, El Salvador, Ghana, Guyana, India, Jordan, Kyrgyzstan, Palestine, Russia, Suriname, Taiwan, Turkey, United States, and Yemen. The case studies relate performance and output within the framework of journalism's core values and its obligations for independence, responsibility, accuracy and truth, as well as monitoring powerful state actors in the sociopolitical and economic arenas.